How Well Do We Know Neonatal Stroke: A Literature Review - Sebayang, Moriko Madadoni; Mouza, Abdurrahman (Asian Australasian Neuro and Health Science Journal (AANHS-J), 2021)
Neonatal stroke can be characterized as a cerebrovascular injury that happens between 20 weeks of fetal life and 28 days post-pregnancy life. The assessed frequency of neonatal stroke is between one of every 1600 and one out of 3000 live births which recommends that the neonatal period is the most engaged lifetime time of hazard for stroke. Utilizing the advances in neuroimaging which have assisted with characterizing explicit neonatal stroke sickness states, several topics consisting of pathophysiology, manifestation, diagnosis, and management of neonatal stroke are systematically reviewed in this study. The results confirm several points, namely: (1) Neonatal stroke is characterized as one of six explicit sickness states based on clinical show and neuroimaging discoveries. (2) Intense indicative assortments normally present with seizures, while assumed neonatal stroke assortments typically present with hemiparetic cerebral paralysis. (3) Across all types of neonatal stroke, causative systems are ineffectively perceived, featuring the requirement for extra investigations just as an alert in allotting causation.